Insights into Generation Z's Perception of Social Media Marketing's Effectiveness on Faith-Based Private School Branding - Carundeng, Stelly Stevanny; Rantung, Danny I.; Mandagi, Deske W. (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The research aims to explore Generation Z's perceptions of social media marketing (SMM) effectiveness for brand building in religious-based private schools, addressing a crucial gap in the literature by examining how SMM influences various facets of brand perception and student behavior within this specific educational niche. Specifically, it investigates SMM's impact on brand attitude, image, intention, and recommendation, utilizing a quantitative descriptive design with primary data collected through surveys and employing probability sampling among 200 high school students via an online survey. Data analysis, conducted using the Structural Equation Model (SEM) with the assistance of the SmartPLS statistical program, reveals a positive and significant relationship between SMM and both brand attitude and brand image, as well as a significant positive correlation between SMM and students' intention to choose a faith-based educational institution and their intention to recommend it. Additionally, a significant positive relationship between brand attitude and brand image is observed, with brand image also displaying a significant positive association with students' intention to choose a faith-based educational institution and their intention to recommend it, thereby providing valuable practical and theoretical insights.